Turning tides in maritime security: coast guard grey zone operations in the East and South China Seas - Ang, Xin Ying (Nanyang Technological University, 2025)
In today’s world, wars need not be fought on the physical front, nor between state military forces – wars and conflicts can be conducted by anyone, and take place in any shape or form. Conflicts between states have taken on a different form, to one that is more ambiguous, and not so much centred around physical force by state military forces. Recent employment of grey zone tactics and behaviours by non-state actors have brought grey zone warfare to the forefront of attention of many states’ military forces and policymakers.